Beliefs regarding diet during childhood illness - Asha D Benakappa; Poojita Shivamurthy (Wolters Kluwer Medknow Publications, 2012)
Background: Fifty percent to 70% of the burden of childhood diarrhea and respiratory infections is attributable to undernutrition. It is compounded by food restriction during illness due to false beliefs, leading to a vicious cycle of malnutrition and infection. In the long run, it decreases the child's productivity, which is an obstacle to sustainable socioeconomic development. Objectives: To assess the dietary practices during different illnesses, to study the role of education, culture and religion in feeding an ill child and to create awareness against detrimental practices. Materials and Methods: A cross-sectional study was undertaken among 126 caregivers of ill children using an open-ended pretested questionnaire. Statistical package for social sciences software was used for data analysis. Simple proportions, percentages and Chi-square were used. Results: Caregivers believed that a child must be fed less during illness. Educational status did not play a role in maintaining beliefs, but elders and religion did. Doctors too were responsible for unwanted dietary restrictions. Media did not have an impact in spreading nutrition messages. Decreased breast feeds, initiating bottle feeds, feeding diluted milk and reducing complementary feeds during illness was widely practiced. Calorie intake during illness was very less and statistically significant. Firmly rooted beliefs about "hot" and "cold" foods lead to restriction of food available at home. Conclusions: Healthy feeding practices were few, and inappropriate ones predominant. Dietary education was overlooked. While planning community-based nutrition programs, firmly rooted beliefs should be kept in mind. Involving the elderly caregivers and mothers actively along with the health workers is the need of the hour.